Identification of Students' Misconceptions and Understanding on Thermochemistry Material with Four-Tier Multiple-Choice Tests - Rosyidah*, Kholifatur; Lutfi, Achmad; Sanjaya, I Gusti Made; Astutik, Julia (Jurnal Pendidikan Sains Indonesia, 2024)
The delivery of chemistry learning lacking meaning and coherence is often associated with the occurrence of misconceptions. These misconceptions when not detected from the start, may persist and affect the understanding of subsequent materials. Therefore, this research aimed to identify misconceptions and understanding of concepts among students, with a focus on factors causing misconceptions about thermochemical materials. A quantitative descriptive approach was used with the four-tier multiple-choice test and questionnaire instruments. The samples comprised students in class XI Science at SMA Kawung 1 Surabaya. The results showed a profile of misconceptions about thermochemical material consisting of system and environment sub-concepts, types of systems, endothermic and exothermic reactions, types of enthalpy, as well as changes in reaction enthalpy. About 15% of students understood the concept, 31% had misconceptions, and 54% did not understand. Factors that caused misconceptions included poor understanding of the material, media used, teachers or methods, and learning resources